Influence of Microbiota on Diabetic Foot Wound in Comparison with Adjacent Normal Skin Based on the Clinical Features. (19th August 2019) - Park, Ji-Ung; Oh, Bumjo; Lee, Jung Pyo; Choi, Min-Ha; Lee, Min-Jung; Kim, Bong-Soo
Abstract : Diabetic foot ulcer (DFU) is a complication experienced by diabetic patients and does not heal well in an altered wound environment. Although diverse microbes in DFU were detected, little is known about their influences on diabetic foot wound (DFW) and the association with the skin microbiota in normal tissue from the same patients according to clinical features. We aimed to analyze the microbiota in normal skin and DFW tissue from the same subject and predict their roles based on clinical features. We analyzed the microbiota in normal skin and DFW tissue from the same subject and compared the associated members of microbiota with clinical parameters. The diversity of skin microbiota was higher than that of DFW tissues, along with compositional differences. In addition, different microbes were associated with clinical features. The proportions of Bacteroidetes, Prevotella, Peptoniphilus, Porphyromonas, and Dialister were higher in the severe groups than of the mild groups, whereas that of Firmicutes was lower in the severe groups. According to wound severity, the microbiota could be related to inflammation, damaging host cell membrane, and pathogenicity through lipopolysaccharide biosynthesis, cellular antigens, and protein digestion metabolism. The predicted DFW microbiota functions according to systemic diabetic status defined by ESRD and HbA1c, differed from those presented by wound severity. Results indicate that the microbiota in normal skin is related to the colonizing microbes in DFW tissue according to clinical features and the different microbes can play important roles in DFW prognosis. This information can be applied to prevent and manage DFW by modulating the microbiota.